Handbook of research on assessment technologies, methods, and applications in higher education - Schreiner, Christopher, 1956- (Hershey, PA : Information Science Reference, 2009)
'This research publication accommodates in-depth studies that elucidate both the prospects and problems of learning assessment in higher education'--Provided by publisher
Includes bibliographical references (p. 418-452) and index
Keywords: College students -- Rating of -- United States -- Handbooks, manuals, etc; Educational tests and measurements -- United States -- Data processing -- Handbooks, manuals, etc